Mobilizing Knowledge - Stoesz, Brenda M; Usick, Brandy (Canadian Perspectives on Academic Integrity, 2022)
We present the first issue of the fifth volume of the Canadian Perspectives on Academic Integrity (CPAI). This issue features the second invited historical article about contract cheating and presents the proceedings from the 2022 Academic Integrity Inter-Institutional Meeting (AIIIM).